Revamping the Role of SMEs’ Digital Financial Management Through Islamic Fin-Tech in Borama - Samsam Hassan (Westscience Press, 2024)
Abstract Small and Medium-sized Enterprises (SMEs) play a vital role in economic growth, particularly in developing countries like Somalia. However, SMEs often encounter financial obstacles due to limited access to conventional banking services adhering to Islamic principles. This study aims to examinate the potential of Islamic Fin-Tech in bolstering Digital Financial Management among SMEs in Borama. Methodologically, the study utilizes quantitative data analysis methods, specifically multiple regression, to examine survey data gathered through purposive sampling. The data is obtained from a total of 2254 small and medium enterprises (SMEs) situated in Borama. Demographic data, including gender, education, occupation, and firm types, are examined alongside the duration of utilizing Islamic fintech solutions. Assumption tests such as normality and multicollinearity tests are conducted to ensure the reliability of the regression model employed. The results indicate a significant adoption of Islamic fintech solutions among SMEs, particularly in recent years. While variables such as Service Accessibility and Digital Banking do not show significant impacts on Digital Financial Management (DFM) due to the internet shortage, SMS Banking and E-Wallet emerge as influential factors that positively affect SMEs' digital financial management performances. Hypotheses testing confirms the significance of SMS Banking and E-Wallet in predicting DFM. The implications of these findings highlight the importance of E-Wallet services and SMS banking in enhancing SMEs' digital financial management. These insights offer valuable implications for financial institutions and policymakers to develop strategies aimed at improving SMEs' digital financial management practices. The study requires for further research to explore additional variables and deepen the understanding of factors that influence SMEs' digital financial management. By understanding the transformative potential of Islamic Fin-Tech, stakeholders can collaborate on designing and implementing measures supporting SMEs, driving economic growth, and aligning with Islamic finance principles. Embracing technological advancements like digital banking and SMS banking can help SMEs overcome financial hurdles and amplify their contributions to economic development. Keywords: SMEs, Digital Financial Management, Islamic Fin-Tech, Borama, Economic development, Fintech, Financial adaptation